Paleoproterozoic basin development on the northern Yilgarn Craton, Western Australia - Occhipinti, S.; Hocking, R.; Lindsay, M.; Aitken, A.; Copp, I.; Jones, J.; Sheppard, Steve; Pirajno, F.; Metelka, V. (Elsevier BV, 2017)
© 2017 A regional tectonic model is presented for the formation and evolution of Paleoproterozoic basins over the northern Yilgarn Craton, integrating new and published regional geological, geochronological, geochemical and geophysical data. The basins formed as a response to both extensional and compressional processes in the early Paleoproterozoic along the craton margin. Early rifting and basin formation coincided with the Ophthalmia Orogeny, the result of the convergence and accretion of the Archean to Proterozoic Glenburgh Terrane with the Pilbara Craton, and led to the formation of the Yerrida Basin at c. 2180 Ma as a single sub-basin containing the Windplain Group. This led to the eventual development of the Bryah and Mooloogool Sub-basins of the Yerrida Basin at c. 2030 Ma, and voluminous extrusion and intrusion of mafic rocks. The depth and nature of the Bryah Sub-basin suggests formation in response to rifting, with its orientation corresponding to the rift axis. Continued rifting along the northern Yilgarn margin resulted in subduction of the Yilgarn Craton beneath the composite Glenburgh–Pilbara craton. Eventual collision was marked by cessation of volcanism and rift-sediment deposition in the Bryah and Mooloogool Sub-basins, the onset of a pro-foreland basin (Padbury Basin) in the west, and approximately NE–SW rifting further east (the Earaheedy Basin), all at c. 2000 Ma. Banded iron-formation and granular iron-formation (Robinson Range and Frere Formations) was deposited much later (c. 1890 Ma) in a large basin that deepened from east to west, spanning the Earaheedy and Yerrida Basins. The deepest parts of this basin coincide with the Bryah Sub-basin, which was the most rifted portion of the Yilgarn Craton in this region. Deposition in all basins probably ceased with onset of the Capricorn Orogeny at c. 1820 Ma.